What's the role of the amygdala in chronic pain?: evidence from magnetic resonance imaging studies in humans - Drabek, Marianne Marta (2020)
The amygdala is most known for its role in fear, threat, relevance processing but also aversive conditioning, is part of nociceptive pathways and has extensive reciprocal connections to many pain-implicated brain areas yet less than 5% of human pain imaging studies report the amygdala. The aim of this thesis is therefore to evaluate the amygdala’s role in pain and pain progression mechanisms. Thus chapter 1 describes this relationship from conceptual and preclinical perspectives and elaborates on possible reasons for its infrequent appearance in human pain literature whilst chapters 4 and 5 evaluate it empirically and try to mitigate some of the knowledge gaps.